Therapeutic potential of thymoquinone in regulating p63, claudin, and periostin in chronic rhinosinusitis with nasal polyps: An animal model study - Ulfa, Loriana; Munir, Delfitri; Rambe, Andrina YM.; Farhat, Farhat; Wardani, Retno S.; Amin, Mustafa M.; Zahara, Devira; Ardinata, Dedi (Narra J, 2025)
High recurrence rate and the necessity for repeated surgical interventions contribute to the chronicity and treatment-resistant nature of chronic rhinosinusitis with nasal polyps (CRSwNP). Thymoquinone, known for its protective effects on epithelial integrity, has not been previously explored in CRSwNP. The aim of this study was to investigate the therapeutic potential of thymoquinone to restore epithelial integrity by assessing p63 transcription factor and claudin protein expressions, as well as periostin mRNA expression in an animal model. An in vivo study using post-test-only control group design was conducted in which male Wistar rats were randomly assigned to three groups, each consisting of 10 animals: healthy group, CRSwNP group, and thymoquinone-treated group for three weeks. Immunohistochemistry was used to analyze the p63 and claudin protein expressions, while periostin mRNA expression was quantified using quantitative reverse transcription polymerase chain reaction (qRT-PCR). This study found that thymoquinone significantly reduced p63 transcription factor expression compared to the untreated CRSwNP group (p=0.009). Claudin protein expression was significantly higher in thymoquinone-treated group compared to CRSwNP group (p=0.007), indicating improved epithelial barrier function. Periostin mRNA expression showed no significant difference between healthy and thymoquinone-treated groups (p=0.564), but a significant decrease was observed in CRSwNP group compared to thymoquinone-treated group (p=0.000) and between the healthy and CRSwNP groups (p=0.002), suggesting attenuation of tissue remodeling and inflammation. In conclusion, thymoquinone could enhance sinonasal epithelial barrier integrity in CRSwNP by downregulating p63 transcription factor, upregulating claudin protein expression, and reducing periostin mRNA expression. These findings emphasize the potential of thymoquinone as a therapeutic agent to mitigate inflammation and tissue remodeling in CRSwNP, warranting further investigation as a novel treatment option.